Estimating the effect of intimate partner violence on women's use of contraception: a systematic review and meta-analysis. - Lauren Maxwell; Karen Devries; Danielle Zionts; Jeanne L Alhusen; Jacquelyn Campbell (PLoS ONE, 2015)
Background Intimate partner violence (IPV) is an important global public health problem. While there is a growing literature on the association between IPV and women's reproductive health (RH) outcomes, most studies are cross-sectional-which weakens inference about the causal effect of IPV on women's RH. This systematic review synthesizes existing evidence from the strongest study designs to estimate the impact of IPV on women's use of contraception. Methods We searched 11 electronic databases from January of 1980 to 3 December 2013 and reviewed reference lists from systematic reviews for studies examining IPV and contraceptive use. To be able to infer causality, we limited our review to studies that had longitudinal measures of either IPV or women's use of contraception. Results Of the 1,574 articles identified by the search, we included 179 articles in the full text review and extracted data from 12 studies that met our inclusion criteria. We limited the meta-analysis to seven studies that could be classified as subject to low or moderate levels of bias. Women's experience of IPV was associated with a significant reduction in the odds of using contraception (n = 14,866; OR: 0.47; 95% CI: 0.25, 0.85; I2 = 92%; 95% CII2: 87%, 96%). Restricting to studies that measured the effect of IPV on women's use of partner dependent contraceptive methods was associated with a reduction in the heterogeneity of the overall estimate. In the three studies that examined women's likelihood of using male condoms with their partners, experience of IPV was associated with a significant decrease in condom use (OR: 0.48; 95% CIOR: 0.32, 0.72; I2 = 51%; 95% CII2: 0%, 86%). Conclusions IPV is associated with a reduction in women's use of contraception; women who experience IPV are less likely to report using condoms with their male partners. Family planning and HIV prevention programs should consider women's experiences of IPV.